(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
The article reveals the features of SWOT analysis as a stage of business planning at the current level of economic development (using the example of PJSC Rosbank). On the basis of the SWOT analysis, the author proposes ways to improve the activities of PJSC Rosbank.